Development of Geogebra-Based Interactive E-Modules to Improve Students' Digital Literacy Abilities - Arie Wahyuni (International Journal of Advance Social Sciences and Education (IJASSE), 2023)
Many students of Ivet University's mathematics education study program think that mathematics courses are very difficult and boring. This happens because students are positioned as listeners in the learning process so that what happens is that the learning process is too monotonous. So far, teaching and learning activities have only used books as a learning resource, an interactive approach will be able to make students more interested in the learning process. One interactive approach in the learning process is using geogebra-based interactive e-modules. The existence of geogebra-based interactive e-modules will further attract students in the learning process and improve students' digital literacy skills. The aim of this research is to produce a geogebra-based interactive e-module to improve students' valid digital literacy skills. The urgency of this research in learning is very important due to the low level of learning resources used in the learning process and the low level of digital literacy for students. The research that will be carried out will have a big impact on student understanding. It is hoped that the development of this interactive e-module will be able to overcome problems that arise in teaching students. It is hoped that limited learning resources can be overcome by having e-modules as a learning medium to prevent misunderstandings arising when teaching integral material. The result of this research is to produce a geogebra-based interactive e-module to improve students' valid digital literacy skills.